Kaitan Beban Kerja Dengan Tingkat Burnout Tenaga Kesehatan Puskesmas Rawat Inap Cimalaka Tahun 2025 - Indra Gunawan; Mahesa Ferdiyana (Nursing News : Jurnal Ilmiah Keperawatan, 2026)
The high workload among healthcare workers in inpatient primary healthcare centers may increase the risk of burnout, which can adversely affect the quality of healthcare services. This quantitative descriptive correlational study examines the relationship between workload and burnout levels among healthcare workers at the Cimalaka Inpatient Community Health Center in 2025. A total of 60 healthcare workers with ? 6 months experience were sampled. Workload was assessed by the NASA-TLX, and and burnout using the Maslach Burnout Inventory (MBI), which assesses three dimensions: emotional exhaustion, depersonalization, and reduced personal accomplishment. Both instruments have established validity and reliability. Univariate analyses described the distribution of workload and burnout scores, while Spearman’s rho correlation tested the associations between variables. The analysis revealed a significant positive association between workload and emotional exhaustion (?=0,315; p=0,014), whereas associations with depersonalization (?=0,180; p=0,168) and reduced personal accomplishment (?= 0,102; p=0,437) were not significant . These findings indicate a significant positive relationship between workload and emotional exhaustion among healthcare workers. In contrast, the relationships between workload and depersonalization, as well as reduced personal accomplishment, were not statistically significant.. The results are expected to inform task allocation planning, stress management interventions, and policies aimed at enhancing staff well-being at Puskesmas Cimalaka.